Meconium and amniotic fluid embolism: Effects on coagulation in pregnant mini-pigs - Petroianu, Georg; Altmannsberger, Stefan H. G.; Maleck, Wolfgang; Aßmus, Hans-Peter; Friedberg, Cora; Bergler, Wolfgang; Rüfer, Roderich (Critical care medicine, 1999)
Objective - A hallmark of amniotic fluid embolism is the induction of coagulation defects. Little is known about the nature of these defects or the causative agent or agents. The purpose of this study was to assess the effects of meconium containing (native) meconium-amniotic-fluid-infusion (MAFI) and meconium free (centrifugated) amniotic-fluid-infusion (AFI) on the coagulation system in the mini-pig model. - Design - laboratory study. - Setting - University institute animal laboratory. - Subjects - Near-term pregnant Gottingen bred mini-pigs in three groups (control, MAFI, AFI) of six animals each. - Interventions - After induction of anesthesia, amniotic fluid was collected by cesarean section in all animals. Depending on the group, animals received either Ringer's solution (control), native amniotic fluid (MAFI), or centrifugated amniotic fluid (AFI) via an ear vein. - Measurements and Main Results - Blood samples were taken from a central vein before infusion (baseline), immediately after infusion, every 10 mins until 90 mins after infusion, and finally, every 20 mins until 150 mins after infusion. The following parameters were measured: Platelets, partial thromboplastin time, prothrombin time, fibrinogen, factors V, VII, VIII, antithrombin III, and protein C. The values relative to baseline in the MAFI and AFI groups were compared with control by rank order test. A p < .05 was considered statistically significant. - Compared with the control group, platelets were lower in the MAFI group (p < .005), PTT was prolonged in both the MAFI and AFI groups (p < .005), fibrinogen was lower in both the MAFI and AFI groups (p < .05), prothrombin index was lower (i.e., prothrombin time was prolonged) in the MAFI group (p < .05), and protein C was lower in the MAFI group (p < .005). - Conclusions - Both MAFI and, to a much lesser extent, AFI cause an activation of coagulation in mini-pigs. The changes induced by meconium-free AFI are probably not sufficient to explain the high mortality of the condition.